Canine Cancers – A Brief Review - C.Vijayalakshmi; K.Vijaya; Aparna Shukla (The Indian Veterinary Journal, 2024)
In this brief review, ten types of cancers that are highly incident on canines are discussed to create awareness among the pet owners. Cancer is believed to be the leading cause of deaths in canines. Care for the canines is essential to protect them from vulnerabilities. For good care and management of pet canines some suggestions are discussed.